Interlaminar fracture property of Moso bamboo strips influenced by fiber distributions in bamboo internode and node. (15th August 2022) - Liu, Chengyang; Liu, Mingxi; Liu, Wen; Li, Zhi; Xu, Feng
Abstract: Bamboo is widely used as sustainable bio-composite material in the construction of houses, pavilions, furniture, and bridges, etc. As a unidirectional fibrous composite, it is usually damaged due to the interlaminar crack, which is directly related to the corresponding microstructure. In this study, the different fracture performances between bamboo internode and bamboo node are researched, as well as the fiber distributions in these zones. For the internode specimens, the results show that specimens with higher fiber contents tend to exhibit higher fracture energy than the case of lower fiber contents, so the fracture energy presents the functional gradient characteristics with fiber content. It is mainly because that more longitudinal vascular bundles make the fracture crack more tortuous and ultimately need more fracture energy. Furthermore, the node specimens have much-strengthened fracture performance than internode specimens with the same fiber contents, due to the radial fibers distributing in the bamboo node. The microscopic observation results indicate that the existence of radial vascular bundles causes the fracture process to include multiple damage modes such as interface delamination, vascular bundle pull-out, and crack deflection and finally play the effect of resisting crack propagation.